On the Analysis of the Contact Conditions in Temporomandibular Joint Prostheses - B. Gonzalez-Perez-Somarriba; G. Centeno; C. Vallellano; L. M. Gonzalez-Perez (Advances in Materials Science and Engineering)
Temporomandibular joint replacement (TMJR) is a complex surgical procedure in which the artificial joints available must assure the anatomical reconstruction and guarantee a good range of the natural temporomandibular joint (TMJ) movements. With this aim, different types of TMJ prostheses, including the stock prosthetic system and custom-made prostheses, are being currently implanted. Although temporomandibular joint replacements (TMJRs) are expected to accomplish their function during a number of years, they might actually fail and need to be replaced. This paper analyzes different design factors affecting the contact stress distributions within the TMJ prosthesis interface, which are consequently involved in their deterioration and final failure of the prosthetic device. With this purpose, a numerical model based on finite elements has been carried out in order to evaluate the stress states attained in different prosthesis configurations corresponding to general types of TMJ prostheses. On the other hand, the actual degradation of resected implants has been evaluated via optical microscopy. The linkage between the numerical simulations performed and experimental evidence allowed the authors to establish the different wear and damage mechanisms involved in the failure of stock TMJ prostheses. Indeed, the results obtained show that the contact stresses at the interface between the mandible and the glenoid fossa components play a key role in the failure process of the TMJR devices.